Relationship among production traits, somatic cell score and temperature–humidity index in the Italian Mediterranean Buffalo. Issue 1 (31st December 2022) - Matera, Roberta; Cotticelli, Alessio; Gómez Carpio, Mayra; Biffani, Stefano; Iannacone, Francesco; Salzano, Angela; Neglia, Gianluca
Abstract: The temperature–humidity index (THI) has been commonly used to analyse heat stress in dairy cattle, but little is known about its effects on buffaloes. In this study, daily milk yield (MY), fat percentage (FP), protein percentage (PP) and somatic cell count (SCC) data from 808 buffalo cows plus environmental temperature and relative humidity were used to investigate the consequence of heat stress. Two mixed models were used to evaluate the impact of THI on MY, FP, PP and log transformed SCC (SCS). The effect of THI was significant for PP, FP and SCS, whereas its interaction with parity was statistically significant for PP and SCS. The relationship between PP and FP and THI was positive but of different magnitude according to the parity. When THI was below 62, an unfavourable effect was observed, especially in primiparous buffalo cows. A significant interaction between SCS and THI across parities was also observed. The effect of THI on MY across parities was not definite but overall a favourable relationship was observed. Our findings depict a susceptibility of buffaloes to low values of THI, suggesting an optimal THI range for water buffaloes between 59 and 63, although some deleterious effects were observed in primiparous buffaloes at THI values lower than 62. Additional investigations are needed to better elucidate the influence of THI on buffalo species. HIGHLIGHTS: The overall effect of THI on buffalo diverges from what commonly observed in dairy cattle Cold stress affects milk and udder health in buffaloes The effect of THI on buffaloes' performance depends on parity, with a larger susceptibility in primiparous than pluriparous buffalo cows Udder health in buffaloes, evaluated using somatic cell count, is also affected by THI